Given,
The expression is,
![f(x)=6x^2+4x-1](https://img.qammunity.org/2023/formulas/mathematics/college/p603ddcp9fv055xzg5mr1s0kaoqfn1k0hz.png)
Substituting x = 0,
![f(0)=6(0)^2+4(0)-1=-1](https://img.qammunity.org/2023/formulas/mathematics/college/l3leidjsrwwkdpjupf7xhl032jjcasv4k2.png)
The value of f(0) is -1.
Substituting x = 2,
![f(2)=6(2)^2+4(2)-1=31](https://img.qammunity.org/2023/formulas/mathematics/college/oowze8acw1h8jiwlftpa3er3ercjxiiwij.png)
The value of f(2) is 31.
Substituting x = -2,
![f(-2)=6(-2)^2+4(-2)-1=15](https://img.qammunity.org/2023/formulas/mathematics/college/wztk92zdbt095oban1ahvrifyguwd5vw4a.png)
The value of f(-2) is 15.
Substituting x = x+1,
![\begin{gathered} f(x+1)=6(x+1)^2+4(x+1)-1 \\ =6(x^2+1+2x)+4x+4-1 \\ =6x^2+6+12x+4x+3 \\ =6x^2+16x+9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gyalbjqnptrocqbk76cgih4cwplqgzb3km.png)
The value of f(x+1) is 6x^2+16x+9.
Substituting x = -x,
![\begin{gathered} f(-x)=6(-x)^2+4(-x)-1 \\ =6(x^2)-4x-1 \\ =6x^2-4x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7liebn1su9wuw3jl85fzjsk26ftlps34st.png)
The value of f(-x) is 6x^2-4x-1.